Maurice Carême, poète du végétal - Tóth, Ágnes (Verbum – Analecta Neolatina, 2023)
In the interpretation of Maurice Carême’s (1899–1978) poetry, nature is often emphasized as a distinct source of his poetic creation. The poet’s work is deeply rooted in nature, especially in the Brabant landscape; this region, its nature, and vegetation are somewhat the ones that shape and influence his thinking. In our reevaluation, we will highlight Maurice Carême’s particular focus on plant life. A rich vocabulary of plant species characterizes this work, evidence of the beauty of the natural world. The botanical aesthetics of this poetry and the paradigms that dominate it are the subjects of our inquiry: the presence of botanical poetic imagery in Carême’s poetry; the inclination toward merging with plant life; and the significance of the form and dynamics of plant life as a model for creation.